Features of constitutional and legal development of Turkestan Soviet Republic. (Journal of actual problems of jurisprudence, 2016)
Constitutional and legal development of Turkestan republic was connected with political development of this area and changed under the influence of the Central Committee. It was made on the basis ofConstitution of RSFSR’s standards The management sphere in the Constitution of Turkestan Autonomous Soviet Socialist Republic of 1918 was considerably free, and in the Constitution of 1920 this freedom was limited and established according to the Central Moscow.
Keywords: control system; administrative district; constitution; republic; judicial authorities; executive committee; legislative activity